2006
DOI: 10.1115/1.2403727
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Prediction of Churning Losses in Geared Transmissions—Preliminary Results

Abstract: A series of formulas are presented which enable accurate predictions of churning losses for one pinion characteristic of automotive transmission geometry. The results are based on dimensional analysis and have been experimentally validated over a wide range of speeds, gear geometries, lubricants, and immersion depths. The case of a pinion-gear pair in mesh has been considered, and it has been proved that, depending on the sense of rotation, the superposition of the individual losses of the pinion and of the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(101 citation statements)
references
References 6 publications
1
99
0
1
Order By: Relevance
“…They indicated that the churning losses mainly consists of four parts: 1) Power losses are generated by the lubricating oil which is in accelerating gear; 2) Power losses are generated by lubricating oil which move in the meshing gear cavity; 3) Power losses are generated by lubricating oil splash in the pool; 4) When the lubricating oil come into meshing gear position, power losses are generated by bending lubricating oil. Changenet et al [8,9] pointed out that most of the current gear churning losses formulas can be more precise calculate the churning losses that were generated in meshing gear or single disk, Petry-Johnson et al [10] obtained same calculation results by analysing the experimental data which is measured under different conditions. Kahraman et al [5] claim that the churning losses is mainly divided into two parts: 1) When the gear is rotated, the power losses were caused by the movement of the lubricating oil stuck on the gear (This part includes three aspects: power losses were generated by interaction of the periphery of gear and lubricating oil; power losses were generated by interaction of the face of gear and lubricating oil; Scroll power losses were generated by lubricating oil in gear cavity); 2) When the gear is meshed, the gap between the two gears is changed and makes the oil being sucked and extruded which cause power losses.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…They indicated that the churning losses mainly consists of four parts: 1) Power losses are generated by the lubricating oil which is in accelerating gear; 2) Power losses are generated by lubricating oil which move in the meshing gear cavity; 3) Power losses are generated by lubricating oil splash in the pool; 4) When the lubricating oil come into meshing gear position, power losses are generated by bending lubricating oil. Changenet et al [8,9] pointed out that most of the current gear churning losses formulas can be more precise calculate the churning losses that were generated in meshing gear or single disk, Petry-Johnson et al [10] obtained same calculation results by analysing the experimental data which is measured under different conditions. Kahraman et al [5] claim that the churning losses is mainly divided into two parts: 1) When the gear is rotated, the power losses were caused by the movement of the lubricating oil stuck on the gear (This part includes three aspects: power losses were generated by interaction of the periphery of gear and lubricating oil; power losses were generated by interaction of the face of gear and lubricating oil; Scroll power losses were generated by lubricating oil in gear cavity); 2) When the gear is meshed, the gap between the two gears is changed and makes the oil being sucked and extruded which cause power losses.…”
Section: Introductionmentioning
confidence: 58%
“…A coupling is used to connect the drive motor to speed and torque sensor. It measures speed and torque of the drive gear by speed and torque sensor, a coupling is used to connected the load motor (9) to speed and torque sensor, it calculates the power losses by the parameters of the input and output speed and torque sensor. Under the same conditions of other parameters, through single-axis actuator changes the axial distance of two gear, it calculates the churning losses by the parameters of speed and torque sensor and bearing block displacement monitor to research the gear churning power losses on different axial distance.…”
Section: Overall Designmentioning
confidence: 99%
“…The variation of viscosity with pressure is based on the Roelands' equation [30], which was also used in the numerical model of Chittenden et al [29], thus embedded in equation (10).…”
Section: Viscous Frictionmentioning
confidence: 99%
“…Several studies have been carried out to determine the churning losses in gearing systems [10][11][12][13]. Changenet and Velex [10] proposed a series of equations to estimate churning losses of a gear for a wide range of speeds, different geometries, lubricants, and immersion depths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation